Impact of prior infection status on antibody response to the BNT162b2 mRNA COVID-19 vaccine in healthcare workers at a COVID-19 referral hospital in Milan, Italy. Issue 12 (2nd December 2021) - Milazzo, Laura; Pezzati, Laura; Oreni, Letizia; Kullmann, Cristina; Lai, Alessia; Gabrieli, Arianna; Bestetti, Giovanna; Beschi, Cristian; Conti, Federico; Ottomano, Cosimo; Gervasoni, Cristina; Meroni, Luca; et al.
ABSTRACT: In Italy, SARS-CoV-2 vaccination campaign prioritized healthcare workers (HCWs) to receive two doses of BNT162b2 vaccine, irrespective of a previous SARS-CoV-2 infection. In this real-life study, we compared the humoral response to BNT162b2 vaccine in HCWs with and without a previous SARS-CoV-2 infection. Of the 407 HCWs enrolled, 334 (82.1%) were SARS-CoV-2-naive and 73 (17.9%) SARS-CoV-2-experienced. Post-vaccine humoral response was detectable in more than 98% of HCWs. Overall, the median level of anti-S IgG in SARS-COV-2-experienced HCWs was twice as high as those of SARS-CoV-2-naive subjects (24641.0 AU/mL [IQR: 15273.0–>40000.0] versus 13053.8 [IQR: 7303.3–20105.8]; p < .001), irrespective of the time elapsed from SARS-CoV-2 previous infection. In a subgroup of SARS-CoV-2-naive and -experienced subjects who received only one dose of the vaccine, the latter showed 32 times higher levels of anti-S IgG compared to the former. Although no serious adverse events have been reported, mild to moderate side effects occurred more frequently after the first dose in the SARS-CoV-2-experienced than in naive subjects (67% versus 42%, respectively; p < .001). Notably, post-vaccination anti-SARS-CoV-2 spike IgG levels ≥20, 000 AU/mL were independently associated with the risk of fever ≥38°C (adjusted odds ratio [aOR] 5.122, 95% CI 2.368–11.080, p < .0001). Our study showed high responsiveness of BNT162b2 vaccine and a relationship between levels of antibody response and reactogenicity. It suggests that a single dose of mRNA vaccine might evoke effective protection in SARS-CoV-2-experienced subjects.